The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1093/cid/ciz831
|View full text |Cite
|
Sign up to set email alerts
|

Routine Screening of Anal Cytology in Persons With Human Immunodeficiency Virus and the Impact on Invasive Anal Cancer: A Prospective Cohort Study

Abstract: Abstract Background The efficacy of screening programs to prevent anal cancer in persons with human immunodeficiency virus 1 (HIV-1) is unclear. Methods To examine the impact of a screening program to detect anal cancer precursors on the incidence of cases of inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 25 publications
2
51
0
4
Order By: Relevance
“…Aktuell untersucht eine prospektive Studie (ANCHOR) die Effektivität von analen IN-Screenings. Große retrospektive Studien zeigen, dass anales Screening und frühzeitige Behandlung von HPV-assoziierten Läsionen die Inzidenz von Karzinomen reduzieren [29,30]. Auf regelmäßige Hautkrebsscreenings unter Zuhilfenahme der Auflichtmikroskopie [31] sollte auch bei der Betreuung von HIV + geachtet werden.…”
Section: Hiv-assoziierte Dermatosenunclassified
“…Aktuell untersucht eine prospektive Studie (ANCHOR) die Effektivität von analen IN-Screenings. Große retrospektive Studien zeigen, dass anales Screening und frühzeitige Behandlung von HPV-assoziierten Läsionen die Inzidenz von Karzinomen reduzieren [29,30]. Auf regelmäßige Hautkrebsscreenings unter Zuhilfenahme der Auflichtmikroskopie [31] sollte auch bei der Betreuung von HIV + geachtet werden.…”
Section: Hiv-assoziierte Dermatosenunclassified
“…Cancer April 1, 2020 not screened at all. 9 The incidence of cancer was found to be higher in the no-screening group. After propensity score adjustment, screening and treatment were found to be significantly protective against cancer, with a hazard ratio of 0.17 (95% CI, 0.03-0.86).…”
mentioning
confidence: 90%
“…The incidence of cancer was found to be higher in the no‐screening group. After propensity score adjustment, screening and treatment were found to be significantly protective against cancer, with a hazard ratio of 0.17 (95% CI, 0.03‐0.86) . Cajas‐Monson et al reported on a large series of patients with HSIL being treated with a “watch‐and‐wait approach,” whereby the HSIL was largely untreated but watched closely for progression .…”
mentioning
confidence: 99%
See 2 more Smart Citations